Acute Myocardial Infarction in Hemophilia A with HIV and Hyperhomocysteinemia- A Rare Case Report - Kachhwaha, Arjun; Rohila, Amit K.; Tripathi, Swapnil; Meena, Durga Shankar; Khichar, Satyendra; Kumar, Deepak (Cardiovascular & Haematological Disorders - Drug Targets, 2022)
Background: Patients with hemophilia have a hypocoagulable state and less chances of thrombus formation. Therefore, they are expected to have a lower cardiovascular mortality than the general population. The lower cardiovascular mortality can be explained by less chances of thrombus formation due to hypocoagulability. Case Presentation: Here, we present a case of a 42-year-old male patient who presented with severe chest pain radiating to the back for 4 days. ECG was suggestive of recent acute anteroseptal myocardial infarction. There was a history of receiving intravenous recombinant factor VIII, 1 hour prior to the onset of chest pain for knee joint swelling. The occurrence of acute coronary syndromes in patients with hemophilia A is uncommon and rarely reported. Conclusion: Here, we report a patient with severe hemophilia A who developed acute myocardial infarction after administration of recombinant factor VIII.
Keywords: HIV Patient